DISTRESS DAN PERFEKSIONISME DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Eka Mariska, Silvia; Fajri Sani, Suharnina; Indah Muslimah, Alfiana (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
The purpose of this study was to determine the effect of Distress and Perfectionism with Somatization on final year students at the Islamic University 45 Bekasi. This study uses a quantitative method with a research design using Pearson Correlation and Multiple Linear Regression with the F Test. The subjects in this study were final year students at the Islamic University "45" Bekasi, totaling 88 students. The results of the instrument reliability test using the Alpha Cronbach formula resulted in ralpha value is 0.963 for somatization, ralpha is 0.916 for Distress and ralpha is 0.923 for perfectionism. The results showed that there was a positive relationship between Distress and Somatization, with a correlation coefficient of 0.224. Furthermore, there is a positive relationship between perfectionism and somatization, with a correlation coefficient of 0.226. The results of the Multiple Linear Regression test between Distress and Perfectionism with Somatization obtained the calculated F result of 3.042, a significant value of 0.053 and the coefficient of determination (R2) of 0.067. This study found that multiple linear regression is not significant but there is a correlation between the variables Distress and Perfectionism affect the Somatization variable which has been proven by comparing the calculated F with the F table